Maternal exome analysis for the diagnosis of oocyte maturation defects and early embryonic developmental arrest. Issue 3 (September 2022) - Capalbo, Antonio; Buonaiuto, Silvia; Figliuzzi, Matteo; Damaggio, Gianluca; Girardi, Laura; Caroselli, Silvia; Poli, Maurizio; Patassini, Cristina; Cetinkaya, Murat; Yuksel, Beril; Azad, Ajuna; Grøndahl, Marie Louise; et al.
ABSTRACT: Research question: Can a methodology be developed for case selection and whole-exome sequencing (WES) analysis of women who are infertile owing to recurrent oocyte maturation defects (OOMD) and/or preimplantation embryo lethality (PREMBL)? Design: Data were collected from IVF patients attending the Istanbul Memorial Hospital (2015–2021). A statistical methodology to identify infertile endophenotypes (recurrent low oocyte maturation rate, low fertilization rate and preimplantation developmental arrest) was developed using a large IVF dataset (11, 221 couples). Twenty-eight infertile women with OOMD/PREMBL were subsequently enrolled for WES on their genomic DNA. Pathogenic variants were prioritized using a custom-made bioinformatic pipeline set to minimize false-positive discoveries through resampling in control cohorts (the Human Genome Diversity Project and 1343 whole-exome sequences from oocyte donors). Individual single-cell RNA sequencing data from 18 human metaphase II (MII) oocytes and antral granulosa cells was used for genome-wide validation. WES and bioinformatics were performed at Igenomix and the National Research Council, Italy. Results: Variant prioritization analysis identified 265 unique variants in 248 genes (average 22.4 per sample). Of the genes harbouring high-impact variants 78% were expressed by MII oocytes and/or antral granulosa cells, significantly higher than for random sample of controls (odds ratio = 5, Fisher's exact P = 0.0004). Seven of the 28 women (25%) were homozygous carriers of missense pathogenic variants in known candidate genes for OOMD/PREMBL, including PATL2, NLRP5 ( n = 2), TLE6, PADI6, TUBB8 and TRIP13 . Furthermore, novel gene–disease associations were identified. In fact, one woman with a low oocyte maturation rate was a homozygous carrier of high-impact variants in ENSA, an essential gene for prophase I meiotic transition in mice. Conclusions: This analytical framework could reveal known and new genes associated with isolated recurrent OOMD/PREMBL, providing essential indications for scaling this strategy to larger studies.